The effectiveness of a systematic approach in the complex treatment of congestive prostatitis with chronic pelvic pain syndrome - I. V. Tikhonov; I. I. Tityaev; D. S. Kasyanov; R. H. Chekushin; K. V. Udalov (Андрология и генитальная хирургия, 2022)
Background. Chronic prostatitis/chronic pelvic pain syndrome remains an urgent urological problem due to unsatisfactory treatment results.Aim. To evaluate the effectiveness of complex therapy of chronic prostatitis using special physiotherapeutic methods of exposure.Materials and methods. The clinical study involved 49 patients aged 22 to 47 years with congestive prostatitis. Two groups were made up of them: group 1 (n = 27) received the main treatment complex – prostate massage, magnetic therapy transcranially and perineally, laser therapy transrectally, chloroethyl applications on the Michaelis rhombus; group 2 (n = 22) – prostate massage and longidase in suppositories rectally. Both groups of patients received standard background spa treatment.Results. At the end of the 14th day course of treatment in group 1 the disappearance of chronic pelvic pain syndrome was noted in 65 % of patients (p p p p (p >0.05), in the rest without significant dynamics.Conclusion. Consistent use of a complex of physiotherapeutic procedures with minimal time intervals between them with a directed effect of synergistic factors not only on problem areas, but also on the central mechanisms of autonomic regulation, affecting the emotional sphere of the patient, leads to a decrease in pelvic pain, which is the leading syndrome in the clinical picture of chronic prostatitis.